Pneumatosis Intestinalis with Pneumoperitoneum Mimicking Intestinal Perforation in a Patient with Myelodysplastic Syndrome after Hematopoietic Stem Cell Transplantation - Keam, Bhumsuk (The Korean Association of Internal Medicine, 2007)
Pneumatosis intestinalis (PI) is an uncommon disorder characterized by an accumulation of gas in the bowel wall, and has been associated with a variety of disorders and procedures. We describe a 35-year-old man who undertook hematopoietic stem cell transplantation due to myelodysplastic syndrome. An abdominal X-ray demonstrated extensive PI with pneumoperitoneum mimicking hollow organ perforation. However, the patient had no abdominal symptoms and there was no evidence of peritoneal inflammation. After two weeks of conservative management, including bowel rest and antibiotics, his pneumoperitoneum resolved spontaneously without any complications. Of the many factors that affect the gastrointestinal tract mucosal integrity, intramural pressure, and bacterial flora-produced intraluminal gas interact to produce PI. If the condition is accompanied by bowel ischemia, portomesenteric venous gas, metabolic acidosis, and abdominal sepsis, or if PI is severe in extent immediate surgical intervention is indicated. The described case supports that a mechanical rather than a bacterial etiology underlies the pathogenesis of PI.